2018
DOI: 10.1021/acsomega.8b00380
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Controlled One-Step Synthesis of Nanostructured LiNi1/3Mn1/3Co1/3O2 Electrodes for Li-Ion Batteries

Abstract: Nanostructured electrodes effectively enhance the kinetics of the charge/discharge process in lithium-ion (Li-ion) batteries. However, the fabrication of these electrodes often involves complex processing steps. This study demonstrates a one-step improved flame spray pyrolysis synthesis approach to directly deposit the most common Li-ion battery cathode material LiNi 1/3 Mn 1/3 Co 1/3 O 2 onto current collectors, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…Nevertheless, a large surface area is also prone to accelerated electrolyte degeneration. Wang et al [105] reported an improvement on the cycle performance by decreasing the surface area via adjusting the precursor concentration. Peralta et al [33] synthesized non-agglomerated sub-micron flake-shape particles with a small ratio of electroactive surface at the edge planes, i.e., a small area for lithium insertion, following the approach to diminish the amount of active surface area.…”
Section: Tailoring Morphology Of Ni-rich Cathode Particlesmentioning
confidence: 99%
“…Nevertheless, a large surface area is also prone to accelerated electrolyte degeneration. Wang et al [105] reported an improvement on the cycle performance by decreasing the surface area via adjusting the precursor concentration. Peralta et al [33] synthesized non-agglomerated sub-micron flake-shape particles with a small ratio of electroactive surface at the edge planes, i.e., a small area for lithium insertion, following the approach to diminish the amount of active surface area.…”
Section: Tailoring Morphology Of Ni-rich Cathode Particlesmentioning
confidence: 99%
“…The Nb-PP separator based cell on the other hand, displayed the potential difference of only 0.15 V corresponding to the redox peaks at 4.14 V and 3.63 V for the first CV scan with reduced potential difference value of 0.19 V and higher peak current of magnitude 0.13 mA. The exceptionally low potential difference indicates the better cycling reversibility 16 . The relatively higher peak current in the latter case could be associated with the improved electrical contact between Nb and Li metal anode which may promote fast Li + transport across the anode|electrolyte interface 65 .…”
Section: Resultsmentioning
confidence: 97%
“…CV measurements were performed for the LNMC cathode based cells in 2.5 V to 4.5 V voltage range at 0.1 mVs −1 . Cells containing PP and Nb-PP separators show a pair of redox peaks corresponding to the Ni 2+ /Ni 4+ during the Li + insertion and removal 16 . The redox peaks for the first CV scan are centered at 4.16 V and 3.65 V respectively, resulting in a potential difference of 0.51 V (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A discharge capacity of 209 mAh g −1 is achieved at 0.2C state of charge conditions. Table also compares the most important studies on the NMC cathode electrodes that can be used in Li‐ion batteries . Herein, we report a systematical study on NMC and NMC‐based composite cathode materials for Li‐ion batteries.…”
Section: Introductionmentioning
confidence: 99%